Low-cost energy-efficient air quality monitoring system using sensor network - Srbinovska, Mare; Mateska, Aleksandra Krkoleva; Andova, Vesna; Krstevska, Maja Celeska; Kartalov, Tomislav (Inderscience Publishers, 2021)
The air pollution has a significant impact on human’s health and global environment. In urban areas the air quality significantly decreased over the past few years. One of the methods for air pollution reduction is by installing green walls, green roofs or by implementing green buildings as plants have capabilities to absorb the particulate matter through their leaves. The main goals of this paper are to present system for air quality monitoring using sensor network technology that can be easily deployed in polluted areas and to examine the influence of the experimental green wall setup to particulate matter more precisely PM10 and PM2.5 concentrations in Skopje, Republic of North Macedonia. Furthermore, the paper presents the preliminary results of the ongoing experiment developed to evaluate the impact of green walls in reduction of air polluting particles' concentrations. The air quality monitoring system can be easily replicated on other locations in the urban areas of Skopje.
Keywords: air quality monitoring system, green walls, sensor network, particulate matter